Asimetri Informasi, Manajemen Laba, dan Pengungkapan Modal Intelektual Terhadap Biaya Modal Ekuitas (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Dian Yulianti; Mintauli Debataraja (UNIVERSITAS RAHARJA, 2022)
This research was conducted to examine the effect of earnings management, intellectual capital and information asymmetry, on the cost of equity capital. The purpose of this study is to determine and analyze the effect of earnings management, intellectual capital and information asymmetry on the cost of equity capital manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016. The sampling technique in this study was purposive sampling. Many of the samples that match the specified criteria are the criteria that are determined as many as 29 companies. Based on the results of the study indicate that: (1) there is no influence of earnings management and intellectual capital against the cost of equity capital (2) there is an influence of information asymmetry on the cost of equity capital